Treatment gaps and potential cardiovascular risk reduction from expanded statin use in the US and England - Ueda, P; Lung, T; Lu, Y; Salomon, J; Rahimi, K; Clarke, P; Danaei, G (Public Library of Science, 2018)
Background: The updated national guidelines for cardiovascular risk assessment and lipid modification in the UK and US expand the indications for statin therapy in primary prevention to adults with moderate risk of cardiovascular disease (CVD) but many adults at high CVD risk remain untreated in both countries. We set out to identify treatment gaps in English and American adults at moderate and high risk of cardiovascular disease (CVD), and to estimate the number of CVD events that would be prevented from expanding statin therapy to those who are currently untreated. Methods: We used nationally representative samples of 10,375 English adults and 7,687 US adults aged 40-75 years and free of existing CVD from the Health Survey for England 2009 -2013, and the National Health and Nutrition Examination Survey 2007-2012 in the US. We used the risk algorithms and the risk thresholds for statin therapy recommended by each country’s national guideline to categorize the survey participants into moderate-risk (≥10% to <20% 10-year risk of CVD in England and ≥7.5% to <20% risk in the US) or high-risk (≥20%risk) and simulated the number of events that would be prevented from expansion of statin therapy to those currently untreated. Results: Close to half of adults at high CVD risk in England (46.0%) and the US (49.7%) were not receiving statins. Expanding statin use to 1.45 million high-risk adults in England would save 101,000 (95% CI=81,000-120,000) CVD events in the next 10 years compared with 128,000 (103,000-154,000) CVD events that would be prevented from expanding treatment to 3.64 million untreated moderate-risk adults. In the US, expanding statin use to 5.27 million untreated high-risk adults would save 384,000 (305,000-461,000) CVD events over 10 years compared with 616,000 (493,000-738,000) CVD events that would be prevented from treating 20.29 million untreated moderate-risk adults. Conclusions: In both England and the US, expanding statin therapy to untreated moderate-risk adults would prevent a comparable number of events as expanding statin use to a much smaller number of currently untreated high-risk adults. A large potential for CVD prevention remains from improving coverage of statin therapy among high-risk adults.